Estrategias educativas innovadoras para fortalecer la lecto-escritura en los estudiantes de 3ro de EGB de la UE Emigdio Esparza Moreno, Babahoyo.2022 - Espinoza Powell, Angela Annabell (2022)
Reading and writing is a fundamental process in student learning, since it allows them to learn to read and write effectively through various pedagogical strategies that facilitate the development of these skills. For this reason, this research was carried out with the purpose of identifying innovative educational strategies that strengthen literacy in 3rd grade EGB students from the EU Emigdio Esparza Moreno. Babahoyo. The methodology applied in this research has a qualitative approach, and is non-experimental in nature; while the types of research used were field and descriptive. It is important to mention that the results of the study were determined through the use of investigative techniques such as direct observation and interviews directed to the teachers of the educational unit under analysis, which provided relevant information in the development of the study. Identifying that teachers do not constantly apply the use of methodological strategies that strengthen the development of reading and writing, nor do they provide educational environments conducive to the development of academic activities; In the same way, it was obtained that teachers rarely serve as a guide during this process; which generates demotivation and lack of interest in students. As a conclusion of this study, it is obtained that the type of strategies that teachers use most frequently are somewhat traditional and even somewhat obsolete, since they promote reading and writing as a mechanical act of teaching; and not as a meaningful learning process